Immunotherapy of targeting MDSCs in tumor microenvironment - Sui, Hongshu; Dongye, Shengyi; Liu, Xiaocui; Xu, Xinghua; Wang, Li; Jin, Christopher Q.; Yao, Minhua; Gong, Zhaoqing; Jiang, Daniel; Zhang, Kexin; Liu, Yaling; Liu, Hui; et al. (Frontiers in Immunology, 2022)
Myeloid-derived suppressor cells (MDSCs) are a group of heterogeneous cells which are abnormally accumulated during the differentiation of myeloid cells. Immunosuppression is the main functional feature of MDSCs, which inhibit T cell activity in the tumor microenvironment (TME) and promote tumoral immune escape. The main principle for immunotherapy is to modulate, restore, and remodel the plasticity and potential of immune system to have an effective anti-tumor response. In the TME, MDSCs are major obstacles to cancer immunotherapy through reducing the anti-tumor efficacy and making tumor cells more resistant to immunotherapy. Therefore, targeting MDSCs treatment becomes the priority of relevant studies and provides new immunotherapeutic strategy for cancer treatment. In this review, we mainly discuss the functions and mechanisms of MDSCs as well as their functional changes in the TME. Further, we review therapeutic effects of immunotherapy against MDSCs and potential breakthroughs regarding immunotherapy targeting MDSCs and immune checkpoint blockade (ICB) immunotherapy.